The need to regulate as compulsory heirs the parents and related children of an assembled family - Shinno Pereyra, Vanessa Elizabeth (2023)
The present work focuses its objectives on carrying out a critical analysis of the right to inherit and its legal regulation mainly to the members that make up the blended families, which according to the pronouncement of the Constitutional Court, recognizes that there is a new type of family where it acquires duties and rights such as kinship by affinity, marriage impediments and minimum assistance for the members of this family; however, it does not urge the Congress of the Republic to make modifications to the civil code, such as establishing special laws with the purpose of regulating duties and rights; and, in addition to this, it is necessary to emphasize the need to regulate parents and related children as forced heirs, since, being a new type of family, it also extends to inheritance law.